Pengaruh pemberian jus wortel terhadap penurunan skala nyeri dismenore primer pada remaja putri - Ariyanti, Vivi Dwi; Veronica, Septika Yani; Kameliawati, Feri (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Based on the data from the World Health Organization (WHO) in 2018, the number of dysmenorrhea cases in the world is very large. The results of a preliminary study conducted at SMA Negeri 1 Seputih Mataram, Central Lampung showed that from 10 teenage girls who experience menstrual pain, a total of 2 teenage girls complained of pain with a mild pain level, 6 teenage girls complained of pain with a moderate pain level, and 2 teenage girls complain of pain with a severe pain level. This research aims to determine the effect of carrot juice consumption on the reduction of primary dysmenorrhea pain levels in teenage girls at SMA Negeri 1 Seputih Mataram, Central Lampung in 2020. The type of this research is a quantitative research with a pre-experimental design namely one-group pretest, one-group posttest design which is given to 20 people by using accidental sampling technique and by giving carrot juice twice a day with 4 hours interval from the first administration. The bivariate test used in this study was the Wilcoxon test. The results of the research show that there is an effect of carrot juice consumption to reduce dysmenorrhea pain (p value 0,001 less than 0.05). It is recommended for health workers to be able to make carrot juice as one of the teenage girls reproductive health treatment programs in order to reduce dysmenorrhea pain. It is expected that the results of this research can be used as a source of information and implementation for the students/teenage girls in an effort to reduce the levels of dysmenorrhea pain through the consumption of carrot juice.